Balance between epithelial and stromal marker expression and distribution in primary culture model of porcine endometrium during real-time cell proliferation - Wojtanowicz-Markiewicz, K; Nawrocki, M J; Brązert, M; Ożegowska, K; Jankowski, M; Rojewska, M; Kocherova, I; Kulus, M; Jeseta, M; Bryja, A; Porowski, L; Bukowska, D; et al. (Journal of biological regulators and homeostatic agents, 2018)
The similarity between humans and pigs, when it comes to tissue morphology, makes Sus scrofa not only a good research model, but also a potential source of cells for tissue engineering. Cell samples obtained from the pig donor, could be influenced in vitro, in order to become a source of tissue material for xenotransplantation, reconstructive and regenerative medicine. Significant amounts of data point to especially major similarities in pig and human reproductive systems. Because of that, particular scientific focus is centered on research concerning porcine COCs, theca and granulosa cells in primary cultures. One of the aspects of the reproductive process, that is still largely undiscovered, is the interaction between preimplantation blastocyst and maternal uterine tissues. In this study, we used molecular analysis techniques, such as RT-qPCR and immunocytochemistry, to analyze the expression and distribution of cytokeratin 18 and panCytokeratins 8, 18 and 19 and vimentin in porcine luminal endometrial epithelial cells, coupled with analysis of their behavior in RTCA. The results have confirmed the presence of epithelial, as well as stromal cell markers in the cells, varying in levels at different stages of culture. They have also given insight into the modes of proliferation and differentiation of studied cells in in vitro culture, as well as providing additional proof for the possible mesenchymal transdifferentiation of epithelial cells.
Keywords: buněčná diferenciace; Humans; endometrium; Female; Models, Biological; epitelové buňky; lidé; modely u zvířat; Biomarkers; zvířata; proliferace buněk; Cells, Cultured; Stromal Cells; buňky stromatu; časové faktory; Swine; Epithelial Cells; biologické markery; ženské pohlaví; kultivované buňky; Cell Proliferation; Cell Differentiation; biologické modely; Models, Animal; Animals; Time Factors; Endometrium; prasata